Kirk-Othmer food and feed technology (Hoboken, N.J., 2007)
This two-volume set features selected articles from the Fifth Edition of Wiley's prestigious Kirk-Othmer Encyclopedia of Chemical Technology. This compact reference features the same breadth and quality of coverage found in the original, but with a focus on topics of particular interest to food technologists, chemists, chemical and process engineers, consultants, and researchers and educators in food and agricultural businesses, alcohol and beverage industries, and related fields
Keywords: Chemistry, Technical,Hóa học, kỹ nghệ